TOLERANSI ANTAR AGAMA DAN ANTAR ETNIS DI DESA MAMAHAK TEBOQ KALIMANTAN TIMUR - Kurnia Y, Yuangga (LP2M IAIN Palopo, 2018)
This paper will research about tolerance inter-religious and inter-ethnic people in Mamahak Teboq Village, East Kalimantan. The choosing of this village based on one of the representative districts in Indonesia with a majority of Protestant believers in the most Moslem population country in the world. Many kinds of accusations intolerance in Indonesia and unfriendly relations between majority-minority became a primary reason for this research. This research used three dimensions of conflict theory (personal/symbolic, relational and structural) as a theoretical framework. This research finds that the majority of non-Moslem in Mamahak Teboq can tolerate every kind of Islamic faiths dan Islamic religious worship from moslem whom are minority and strangers. That case answered an accusation which said that another religious people (in this context is Christians) could not show any tolerance in a majority position.